Interindividual uniformity and variety of the “Writing center”: A functional MRI study - Sugihara, Genichi; Kaminaga, Tatsuro; Sugishita, Morihiro (NeuroImage (Orlando, Fla.), 2006)
Our aim is to investigate the neural substrates for writing using fMRI (twenty right-handed subjects). We assumed that common areas involved in both writing with right and left hands are crucial to the central process of writing. We employed Japanese phonograms ( Kana), in which phoneme–grapheme conversion would be extremely simple. Brain activation was examined under three conditions: (1) written naming with the right hand (WR), (2) written naming with the left hand (WL), and (3) naming silently (NA). While the comparison of WR to NA (WR > NA) exhibited activation only in the left frontoparietal area, the WL > NA comparison exhibited broader activation than the WR > NA comparison, i.e., the left frontoparietal area except the motor and sensory areas and the right frontoparietal area. A conjunction analysis in SPM2 revealed common areas of activation across the WR > NA and WL > NA comparisons, which are assumed to be crucial to writing. In the group analysis, three areas were found to be activated: the posterior end of the left superior frontal gyrus, which is superior and posterior to Exner's center; the anterior part of the left superior parietal lobule; and the lower part of the anterior limb of the left supramarginal gyrus. In the single-subject analysis, whereas the first two of the above three areas were found to be crucial for writing in all individuals, an interindividual inconsistency of involvement with writing was observed in three areas: the lower part of the anterior limb of the left supramarginal gyrus (60% involved); the right frontal region (47%); and the right intraparietal sulcus (47%).